2023
DOI: 10.3389/fpubh.2023.1134032
|View full text |Cite
|
Sign up to set email alerts
|

Health related quality of life among people with mental illness: The role of socio-clinical characteristics and level of functional disability

Abstract: BackgroundPeople with mental illness (PWMI) have declining health related quality of life (HRQoL), which is frequently equivalent to or greater than that of medical disorders. Although, HRQoL is rapidly being recognized as an essential treatment outcome indicator in modern psychiatry, research on the identification and significance of factors impacting QoL in PWMI is still in its early stages.ObjectiveThe aim of this study was to identify predictors of HRQoL among people with mental illness who underwent outpa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 72 publications
2
13
0
Order By: Relevance
“…Our study revealed significant associations between the degree of disability and various demographic attributes of individuals with disabilities, which generally align with previous findings on factors such as age ( Fong, 2019 ), education level ( Brigola et al, 2019 ), marital status ( Defar et al, 2023 ), and employment status ( Nevala et al, 2019 ). First, as we age, natural processes of organ and system degradation occur in the body.…”
Section: Discussionsupporting
confidence: 91%
“…Our study revealed significant associations between the degree of disability and various demographic attributes of individuals with disabilities, which generally align with previous findings on factors such as age ( Fong, 2019 ), education level ( Brigola et al, 2019 ), marital status ( Defar et al, 2023 ), and employment status ( Nevala et al, 2019 ). First, as we age, natural processes of organ and system degradation occur in the body.…”
Section: Discussionsupporting
confidence: 91%
“…importantly note that QoL is a ‘subjective measure that is not necessarily reduced in severe diseases’ (p. 2079). QoL in PLWMI is unsurprisingly multifaceted, with social support, occupation and marital status among contributing factors, 24 and person‐specific. In examining the complexity of QoL for PLWMI, the role of stigma, particularly internalised stigma, 25 on QoL outcomes 26 has been emphasised.…”
Section: Discussionmentioning
confidence: 99%
“…Mental illnesses have a significantly negative influence on QOL. [5] As the QOL of psychiatric patients is worse than healthy controls, [6] and it improves following interventions, QOL has been used in clinical practice and research as an outcome measure. There are many challenges in measuring the QOL, as it is rather a subjective concept that needs to be assessed objectively, psychopathologies can influence the assessments considerably, and as multiple contributing factors, it is essential to assess the contribution from the health separately.…”
Section: Quality Of Life and Mental Healthmentioning
confidence: 99%